Use Study on Slight Beam Reinforced Concrete Floor Plate In Lieu of Scondary Beam - Hery Riyanto; Sugito SUGITO; Lilies Widodjoko; Sjamsu Iskandar (Bandar Lampung University (UBL), 2013)
Use of false beams on reinforced concrete slab instead of the joist is an innovation in the construction of reinforced concrete slab. Where the study was made by using 4 samples of precast concrete slab specimens (PBP). Ie: P1 type - plate only, type P2 - plate with joists, type P3 - small plates with slight beams, type P4 - plate with big apparent beam. The fourth specimen samples made using the Batu Raja cement, sand from Gunung Sugih, and local split Bandar Lampung in the Civil Engineering Laboratory of UBL. The fourth test specimen samples was conducted at the Laboratory of Civil Engineering Unila using method one point load that is placed in the center - the center span in order to get the load and the maximum deflection and crack patterns. The data obtained are used to verify the theoretical calculations. Conclusions will be given at the end of writing.